Structured Pd/γ-Al2O3 Prepared by Washcoated Deposition on a Ceramic Honeycomb for Compressed Natural Gas Applications. (23rd June 2015) - Adamowska, Małgorzata; Da Costa, Patrick
Abstract : The preparation of a coating procedure was studied, from the washcoating with γ -alumina to the deposition of palladium by excess solvent or incipient wetness impregnation. The powder and the washcoat layers were studied by different characterisation techniques such as SEM, BET surface area, and XRD. Vibration-resistance and heat-resistance were also evaluated. It was shown that the alumina layer is quite well deposited on the channel walls (SEM images). However, a detachment of the washcoat layer was observed after ultrasound treatment. It was proved that the monolith Pd impregnation method by incipient wetness impregnation is more efficient. The presence of palladium was confirmed using HRTEM, the palladium was present under the Pd (II) oxidation state, and the size of PdO particles varies between 2.5 and 3.1 nm. The catalytic properties of the monolith catalyst were carried out using temperature programmed surface reaction (TPSR). The efficiency of the procedure of the monolith catalyst preparation was confirmed by comparing the activity of the prepared catalyst with the one of a model catalyst.